Lord Broghill and the Scottish Church, 1655–1656 - Buckroyd, Julia (The journal of ecclesiastical history, 1976)
Small attention has generally been paid to the activities of Roger Boyle, Lord Broghill, during his year in Scotland from September 1655 to September 1656. In particular, his negotiations with the Protester and Resolutioner ministers have not been supposed any more or less successful than those, for example, of Lillburne or Monck, but merely another stage in the Cromwellian government's ineffectual urgings towards a settlement of the dispute in the Church.